Does Watching TV Make Us Happy? - Bruno S. Frey; Christine Benesch; Alois Stutzer (Center for Research in Economics, Management and the Arts (CREMA), 2005)
The paper studies a major human activity - that of watching TV - where many individuals have incomplete control over, and foresight into, their own behavior. As a consequence, they watch more TV than they consider optimal for themselves and their well-being is lower than what could be achieved. Mainly people with significant opportunity costs of time regret the amount of time spent watching TV. They report lower subjective well-being when watching TV for many hours. For others, there is no negative effect on life satisfaction from watching TV. Long hours spent in front of a TV are linked to higher material aspirations and anxiety and therewith lower life satisfaction.
Keywords: D12; I31; 330; Life satisfaction; mispredicting utility; revealed behavior; self-control problem; TV consumption